Extended School Day Development in Primary Level Evaluation - Chaljub-Hasbún, Jeanette (2021)
This research has been financed by Universidad del Caribe (UNICARIBE). The general objective is to evaluate the conditions in which the Extended School Day (ESD) is being developed in the Second Cycle at Primary Level in the Dominican Republic. Among the specific objectives are to identify the use and management of spaces in schools that apply ESD, analyze the pedagogical time management, and evaluate the profile of the teacher responsible for the activities in the afternoon session. This investigation was framed within the mixed approach and includes a descriptive scope. A survey was given to 18 teachers, distributed among the five participating centers with their respective principals. Also, the principals were interviewed. The data obtained led to the conclusion that most participating teachers affirm that the spaces in the schools are not adequate for the development of ESD workshops. Therefore, it is not possible to obtain the expected results in this modality and carry out productive activities in order to achieve the expected learning outcomes through the evening period. Among the opportunities for improvement, we can remark that both interviewed principals and participating teachers maintain that is very important the correct planning of workshops or optional courses focused on meaningful activities for the students’ training, including appropriate management of time and space in the school center.